Swelling of rubber in blends of diesel and cottonseed oil biodiesel. (April 2021) - Kittur, M.I.; Andriyana, A.; Ang, B.C.; Ch'ng, S.Y.; Mujtaba, M.A.
Abstract: Biodiesel has emerged as one of the major sources of renewable energy in automotive applications substituting the convention diesel. However, the compatibility of biodiesel and rubber components remains a major concern. Indeed, it is found that biodiesel tends to swell rubber components resulting to their faster degradation. Thus, studies focusing on the compatibility of newly developed biodiesel are essential for rubber durability. Along this line, the main purpose of the present study is to investigate the swelling characteristics of rubber in cottonseed oil biodiesel. Two types of unfilled and filled rubbers are considered: natural rubber (NR) and polychloroprene rubber (CR). For filled rubbers, two carbon black contents are used: 25 and 40 phr. The rubber samples are immersed in conventional diesel fuel, biodiesel and diesel-biodiesel blends for 1000 h at room temperature (25 °C). The evolutions of rubber mechanical properties such as hardness, tensile modulus and tensile strength are investigated as well as the macroscopic stress-strain characteristics. For both rubbers, it is found that the decrease in the mechanical properties becomes more significant as the biodiesel content increases. Finally, a continuum model predicting equilibrium swelling proposed by Ch'ng [S.Y. Ch'ng. Coupling between diffusion of biodiesel and large deformation in elastomers: from experimental investigation to constitutive modeling. Ph.D. Thesis. University of Malaya, Malaysia. 2014] is adopted to simulate the effect of carbon black on the stress-free equilibrium swelling of rubber. Highlights: Swelling increases with the COME concentration in the biodiesel blends. Carbon black provides better retention of mechanical responses in swollen elastomers. Swelling in diesel and biodiesel blends leads to degradation of mechanical properties of elastomers. A continuum model adopted to predicted equilibrium swelling of elastomers.